Motivation and citizenship performance of generation X & Y in electric and electronic industry - Tan, Shen Kian (2012)
Malaysia is facing distinct competition where national competitive advantages are now focus on potential to produce, acquire, utilize and disseminate knowledge rather than labour, land and natural resources. In order to support implementation of knowledge-based economy, this study serve a purpose to examines the relationship between Motivation and Citizenship Performance for Generation X and Generation Y employees. Quantitative approach was used in this research. A set of structured questionnaire were distributed based on Cluster Sampling method to reach 124 respondents from two multinational electronic manufacturers. Seven Intrinsic and Extrinsic Motivation Factors that adduced in this research are Achievement, Recognition, Work Itself, Promotion, Company Policy and Administration, Pay and Benefit, and Work Condition; while Citizenship Performance is measured by 15 items scale of Organization Citizenship Behaviour (OCB) that combine all causations as one unit of variable. This research exposed the extents of satisfactions for Intrinsic and Extrinsic Motivation Factors as well as levels of Citizenship Performance for Generation X are higher than Generation Y respondents. The following Pearson Correlation further revealed a positive correlation between Intrinsic Motivation Factors towards Citizenship Performance and a negative correlation between Extrinsic Motivation Factors towards Citizenship Performance on Generation X respondents. Conversely, Generation Y respondents have found a contrariwise correlation for the two Extrinsic and Intrinsic Motivation Factors towards Citizenship Performance. This study concluded that the two Generations are significantly different in Motivation Factors as encouragements towards Citizenship Performance.